Quasar lenses and pairs in the VST-ATLAS and Gaia. Issue 2 (13th December 2017) - Agnello, A; Schechter, P L; Morgan, N D; Treu, T; Grillo, C; Malesani, D; Anguita, T; Apostolovski, Y; Rusu, C E; Motta, V; Rojas, K; Chehade, B; et al.
Abstract: We report on discovery results from a quasar lens search in the ATLAS-DR3 public footprint. Spectroscopic follow-up campaigns, conducted at the 2.6 m Nordic Optical Telescope (La Palma) and 3.6 m New Technology Telescope (La Silla) in 2016, yielded seven pairs of quasars exhibiting the same lines at the same redshift and monotonic flux ratios with wavelength (hereafter NIQs, nearly identical quasar pairs). Magellan spectra of A0140−1152 (01 h 40 m 03^s_. 0–11 d 52 m 19^s_. 0, z s = 1.807) confirm it as a lens with deflector at z l = 0.277 and Einstein radius θE = (0.73 ± 0.02) arcsec. Follow-up imaging of the NIQ A2213−2652 (22 h 13 m 38^s_. 4–26 d 52 m 27^s_. 1) reveals the deflector galaxy and confirms it as a lens. We show the use of spatial resolution from the Gaia mission to select lenses and list additional systems from a WISE- Gaia -ATLAS search, yielding three additional lenses (02 h 35 m 27^s_. 4–24 d 33 m 13^s_. 2, 02 h 59 m 33 s –23 d 38 m 01^s_. 8, 01 h 46 m 32^s_. 9–11 d 33 m 39^s_. 0). The overall sample consists of 11 lenses/NIQs, plus three lenses known before 2016, over the ATLAS-DR3 footprint (≈3500 deg 2 ). Finally, we discuss future prospects for objective classification of pair/NIQ/contaminant spectra.